The role of music in young learners’ oral production in english (2010)
This article reports on a study conducted at Universidad Nacional de Colombia in the foreign language extension courses. The author shows how young learners who study English in this program can develop their oral production by making and listening to music. The study took place in the first semester of 2009 and followed the qualitative and descriptive approaches to classroom research. The author describes how young learners view music as a ludic tool that will improve their oral performance and how the activities applied by a music teacher help to reinforce the language topics studied in other English classes. Key words: Music in English learning, teaching young learners, oral production Este artículo reseña un estudio realizado en la Universidad Nacional de Colombia en los cursos de extensión de lenguas extranjeras. El autor muestra cómo los niños y jóvenes que estudian inglés en este programa pueden desarrollar su producción oral creando y escuchando música. El estudio se realizó en el primer semestre del 2009 y siguió los enfoques cualitativo y descriptivo para la investigación en el aula. El autor describe cómo perciben los niños y jóvenes la música como una herramienta lúdica para mejorar su desempeño oral y cómo las actividades musicales que realiza un profesor de música ayudan a reforzar los temas estudiados en otras clases de inglés. Palabras clave: la música en el aprendizaje del inglés, enseñanza del inglés a niños y jóvenes, producción oral